The intention and the reality: A commentary on the not-for-profit reform agenda in Australia - Pilcher, Robyn; Gilchrist, D. (Routledge, 2018)
The not-for-profit (NFP) sector is a critical part of the social infrastructure of a developed country. It is a sector that has a long history and, in the Australian context, was early recognised by the establishment of legislation designed to facilitate the incorporation of associations. Over time, the legislation in Australia was changed to meet changing perceptions relating to the governance, regulation and supervision of these organisations. The focus of NFP organisations has largely been recognised to be related to mission—NFP organisations are provided tax relief and other advantages as they are seen to provide critical services and supports that enhance our civil society while members cannot appropriate profits or assets generated out of the operations. However, in the last five years or so, the general perception regarding the regulation and supervision of NFP organisations has related to what might be called commercial foci. Part of this change is the result of the increasingly commercial nature of the relationship between government and the NFP sector, wherein government seeks to procure services from the sector commensurate with its policy objectives as they may be from time to time. This chapter examines the development of reform at the national and sub-national levels in Australia related to NFP organisations over time, in order to assess the nature of NFP organisations themselves, the drivers of reform, and the impact such reforms are likely to have on mission priorities in particular. We find that, while NFP organisations are sui generis and have their provenance in mission centricity, without focusing on this mission as part of the regulatory framework, the drift toward commercial values is likely to reduce the suitability of NFP organisations to their social task.